Retrograde Type A Aortic Dissection After Thoracic Endovascular Aortic Repair: A Systematic Review and Meta‐Analysis - Chen, Yanqing; Zhang, Simeng; Liu, Lei; Lu, Qingsheng; Zhang, Tianyi; Jing, Zaiping (Journal of the American Heart Association, 2017)
Background Retrograde type A aortic dissection (RTAD) is a potentially lethal complication after thoracic endovascular aortic repair (TEVAR). However, data are limited regarding the development of RTAD post‐TEVAR. This systematic review aims to define the incidence, mortality, and potential risk factors of RTAD post‐TEVAR. Methods and Results Multiple electronic searches were performed. Fifty publications with a total of 8969 patients were analyzed. Pooled estimates for incidence and mortality of RTAD were 2.5% (95% confidence interval [CI], 2.0–3.1) and 37.1% (95% CI, 23.7–51.6), respectively. Metaregression analysis evidenced that RTAD rate was associated with hypertension (P=0.043), history of vascular surgery (P=0.042), and American Surgical Association (P=0.044). The relative risk of RTAD was 1.81 (95% CI, 1.04–3.14) for acute dissection (relative to chronic dissection) and 5.33 (95% CI, 2.70–10.51) for aortic dissection (relative to a degenerative aneurysm). Incidence of RTAD was significantly different in patients with proximal bare stent and nonbare stent endografts (relative risk [RR]=2.06; 95% CI, 1.22–3.50). RTAD occurrence rate in zone 0 was higher than other landing zones. Conclusions The pooled RTAD rate after TEVAR was calculated at 2.5% with a high mortality rate (37.1%). Incidence of RTAD is significantly more frequent in patients treated for dissection than those with an aneurysm (especially for acute dissection), and when the proximal bare stent was used. Rate of RTAD after TEVAR varied significantly according to the proximal Ishimaru landing zone. The more‐experienced centers tend to have lower RTAD incidences.